2019
DOI: 10.9734/ibrr/2019/v9i230098
|View full text |Cite
|
Sign up to set email alerts
|

ABO Blood Group System: Its Association with Anthropometric Indices among Young Adults of Yoruba Ethnicity

Abstract: Introduction: The ABO blood group system is unique in immunology and haematology because it is the only system in which antibodies are consistently and predictably present in the serum of normal individuals whose red cells lack the antigens. Several epidemiological studies have reported that the distribution of different ABO blood groups vary markedly among the populations of different geographical areas reflecting racial differences. Aims: The aim of this study was to determine the association between A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The present study revealed a statistically significant difference only in ABO/ Rh blood group percentages (Rh +ve & Rh -ve) among pre-and post-menopausal hypertensive women. However, no statistically significant association between ABO/ Rh blood groups and hypertension indices was obtained which was consistent with recent findings [24,[27][28][29]. This highlights the complex interplay between biological factors, particularly hormonal changes, genetic factor, cardiovascular, demographic, and sample-related factors [10].…”
Section: Disscusionsupporting
confidence: 88%
“…The present study revealed a statistically significant difference only in ABO/ Rh blood group percentages (Rh +ve & Rh -ve) among pre-and post-menopausal hypertensive women. However, no statistically significant association between ABO/ Rh blood groups and hypertension indices was obtained which was consistent with recent findings [24,[27][28][29]. This highlights the complex interplay between biological factors, particularly hormonal changes, genetic factor, cardiovascular, demographic, and sample-related factors [10].…”
Section: Disscusionsupporting
confidence: 88%
“…A recent study that relies on obesity indices such as, lean body mass (LBM) other than BMI reported significant difference in the distribution of ABO or Rh blood groups (Siddiqui et al, 2019) and this association was also reported by other studies (Suadicani et al, 2005;Eren and Çeçen, 2019). In a previous study no statistical difference were reported between blood groups and obesity although sample was small and 85% were females (Asafa et al, 2019).…”
Section: Abo Rh Gender and Golden Ratiomentioning
confidence: 76%